2003
DOI: 10.1182/blood-2003-05-1408
|View full text |Cite
|
Sign up to set email alerts
|

Ifosfamide impairs the allostimulatory capacity of human dendritic cells by intracellular glutathione depletion

Abstract: IntroductionIfosfamide, which is a commonly used antineoplastic agent in the treatment of malignancies such as lymphomas, breast cancer, and sarcomas [1][2][3] has been shown to reduce glutathione (GSH) levels in various cell types. 4,5 Previously, we demonstrated that ifosfamideinduced GSH depletion in T cells and natural killer (NK) cells was accompanied by a corresponding decrease in T-cell function and NK-cell cytotoxicity. 6,7 In vivo ifosfamide is metabolically activated by hepatic mixedfunction oxidases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 38 publications
3
30
1
Order By: Relevance
“…Recent studies have revealed that ROS play a critical role in DC activation and maturation (15)(16)(17)(18)(19)(20)(21). Boldogh and colleagues demonstrated the critical role of ROS generated by the intrinsic NADPH oxidase activity of RWE in enhancing antigen-induced allergic airway inflammation in mice, possibly by activating airway epithelial cells (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that ROS play a critical role in DC activation and maturation (15)(16)(17)(18)(19)(20)(21). Boldogh and colleagues demonstrated the critical role of ROS generated by the intrinsic NADPH oxidase activity of RWE in enhancing antigen-induced allergic airway inflammation in mice, possibly by activating airway epithelial cells (13).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Peterson and colleagues showed that the depletion of glutathione in murine antigen-presenting cells in vivo resulted in lower Th1 activity and higher Th2 activity (14). Other studies confirmed that DCs rely on intracellular redox state for proper development and function and that DC activation and associated immune functions are influenced by oxidative stress (15)(16)(17)(18)(19)(20)(21). Oxidative stress occurs when the oxidants overwhelm antioxidant defenses.…”
mentioning
confidence: 96%
“…8 In addition, GSH depletion reduces the expression of costimulatory molecules in DCs and modifies their ability to stimulate allogeneic Mixed leukocyte reaction (MLR) responses of T cells. 9 In vivo, GSH depletion in antigen-pulsed DCs interferes with the delayed-type hypersensitivity (DTH) response, probably as a consequence of IL-12 repression. 10 H 2 S is the final metabolite of the trans-sulfuration pathway.…”
Section: Introductionmentioning
confidence: 99%
“…134 Variations on these themes most likely result in altered function of other reconstituted immune effector cells. 135 However, such mechanisms of immune dysfunction post-HSCT currently remain largely undefined. 136 Nonetheless, consequences of immune dysfunction in the HSCT recipient include delayed engraftment or even graft failure, disease relapse, and infection.…”
Section: Mechanisms Of Immune Effector Dysfunction and Their Implicatmentioning
confidence: 99%